الموريسكي... معضلة الهوية ورحلة البحث عن الذات - طبيشة, حنينة (University of El-oued, 2021)
إذا كانت الهوية تمثل نسقا من المعايير التي تشكل مجتمعة هوية الذات ووحدتها، وكل انفصال ونفي لواحد من هذه المعايير يؤدّي بالضرورة إلى اغتراب الذات وتشظّيها ما يجعل الذات متململة ومحتارة، لذا فهي تقرّر بوعيها التاريخي تجاوز حالة التململ والحيرة إلى مرحلة جمع هذا الشتات عبر المواجهة والعودة إلى ذلك الشرخ، والكتابة عنه؛ باعتبار الكتابة وجودا مستمرا في الزمان والمكان، وهذا ما تحاول رواية الموريسكي الاقتراب منه عبر الاشتغال على أزمة الموريسكيين التي تقدم عبر شخصياتها نماذج متفاوتة الهشاشة لذا يختار البطل بوعيه التاريخي أن يقترب من هذه الشروخات الهوياتية عبر الكتابة عنها وتخليدها للأجيال القادمة. Considering that identity represents a set of collective standards that constitute the unity of the self, then separating or removing one of these standards necessarily leads to the alienation and fragmentation of the self, which consequently results in a state of restlessness and confusion. Moreover, it is believed that historical awareness about the subject of identity leads the self to move beyond the aforementioned state to the stage of collecting this diaspora through confrontation and understanding, and then write about it. The act of writing is a continuous process that is presented in time and space, and this is what the Moriscos novel attempts to approach by working on the crisis of the Moriscos which is shown through its varied characters differing in fragility, so the protagonist, with his historical awareness, chooses to approach these identity cracks by writing about them and perpetuating them for future generations.
The Moresque And The Dilemma Of Identity In The Journey Of Self-search
مقال. مجلة القارئ للدراسات الأدبية والنقدية. مج04. ع.02. جامعة الوادي
Keywords: الهوية ; الاغتراب ; الذات ; الموريسكي ; التاريخ; identity ; Alienation ; Self ; Moresque ; History